Dust concentration distribution and analysis of influencing factors in the heading face of Shangwan coal mine - Li, Yufu; Wang, Jie; Li, Zhibin; Mo, Haitao (Frontiers in Earth Science, 2024)
Dust concentration in coal mine roadways significantly affects worker safety and health. Effective dust control is critical for optimizing the mine ventilation system and creating a safer working environment. This study investigates the impact of ventilation duct arrangements on dust concentration in a heading face, aiming to identify the optimal configurations for minimizing dust levels and enhancing worker safety. Using numerical simulations based on the gas-solid two-phase flow model in Fluent, we analyzed the effects of varying duct outlet distances and heights on airflow patterns and dust dispersion. Mesh generation, grid independence verification, and detailed parameter settings ensured accuracy and reliability of the simulation results. Results indicate that positioning the duct outlet 8 m from the heading face reduces dust concentration to approximately 39 mg/m³, while setting the duct height at 1.5 m notably decreases dust levels in the worker breathing zone. A mesh density of 576,449 cells ensured convergence and computational efficiency with an error margin within 2%. The findings provide practical insights into ventilation system optimization for coal mine heading faces, contributing to improved occupational health and operational safety. Future research should focus on validating these results through field experiments and addressing complex real-world conditions.